Validation of the HAS-BLED scale for the assessment of bleeding risk in patients on anticoagulation therapy with a diagnosis of venous thromboembolic disease - Stephanie Ortiz-Gómez; Paula Ruiz-Talero; Oscar Muñoz (Permanyer, 2024)
Background: Several models have been developed to assess bleeding risk in patients with venous thromboembolism, such as HAS-BLED, but their external validity has not been adequately assessed. Objective: The objective of the study was to evaluate the discriminative ability and calibration of the HAS-BLED scale for predicting 1-month bleeding risk in patient's anticoagulated for venous thromboembolism. Materials and Methods: External validation study of a prediction model based on a retrospective cohort of patients with venous thromboembolism treated between November 2019 and January 2022. Calibration of the HAS-BLED scale was evaluated using the Hosmer-Lemeshow test and the ratio of observed to expect events within each risk category. Discriminatory ability was assessed using the area under the curve (AUC) of a receiver operating characteristic curve. Results: We included 735 patients (median age 64 years, female sex 55.2%), pulmonary embolism was diagnosed in most patients (60.7%), and 4.9% presented bleeding events. Regarding calibration, the HAS-BLED scale systematically underestimates the risk both in the general population (ROE 3.76, p < 0.001) and in cancer patients (ROE 4.16). The Hosmer-Lemeshow test rejected the hypothesis of adequate calibration (p < 0.001). Discriminatory ability was limited both in the general population (AUC = 0.57, 95% confidence interval [CI]: 0.48-0.66) and in the subgroup with active cancer (AUC = 0.53, 95% CI: 0.36-0.69). Conclusion: The HAS-BLED scale in patients with venous thromboembolism underestimates the risk of bleeding at 1 month and has a low ability to discriminate high-risk patients. Cautious interpretation of the scale is recommended until additional evidence is available.